The Influence of Price, Product Quality and Promotion on the Decision to Purchase Ventela Shoes at the Schulkinder Store in Ungaran City - Aprilia, Annisa Onik; Purwanto, Edy; Baskara, Andika (Economics and Business International Conference Proceeding, 2024)
Thesis entitled The Influence of Price, Product Quality and Promotion on the Decision to Purchase Ventela Shoes at the Schulkinder Store in Ungaran City. Using a non-probability sampling method with a sample size of 100 respondents. The data collection technique uses a questionnaire processed using SPSS version 26. Data analysis uses multiple linear regression. The results of this research show, based on hypothesis testing that price variables, product quality and promotion have a positive and significant effect on purchasing decisions. Based on partial hypothesis testing, the influence of price variables has an influence on purchasing decisions. The product quality variable has a positive and significant effect on purchasing decisions. The promotion variable has no effect on purchasing decisions. The results of the coefficient of determination (Adjusted R Square) show that the influence of product quality price and promotion on purchasing decisions is 39.4%, while the remaining 60.6% is influenced by other independent variables not included in this research